Assessment of Severity of Acute Pancreatitis Using Modified Computed Tomography Severity Index and Revised Atlanta Classification and Their Association with Clinical Outcome Parameters - Swasti Jain; Ankur Malhotra; Shruti Chandak; Deepti Arora; Aman Taneja (Acta Medica International)
Introduction: Acute pancreatitis (AP) is a serious gastrointestinal condition with significant morbidity and mortality. It can lead to various complications and is commonly diagnosed using laboratory tests and contrast-enhanced computed tomography (CT) scans. This study evaluates the efficacy of the Modified CT Severity Index (MCTSI) and the neutrophil-to-lymphocyte ratio (NLR) in predicting the severity of AP compared to the Revised Atlanta Classification (RAC). In addition, we will also assess concordance of MCTSI and RAC with NLR. Materials and Methods: After approval from IEC, this prospective observational study, conducted over 18 months at Teerthanker Mahaveer Medical College Hospital, Moradabad, Uttar Pradesh, included 65 adult patients clinically diagnosed with AP. All participants satisfying the inclusion criteria were enrolled after taking a written informed consent and they underwent standard laboratory tests (including a complete blood count) and radiological evaluation (including CT scan performed using 128-slice scanner Ingenuity CT, Philips Healthcare) during their hospital stay. The primary outcome measures were the sensitivity, specificity, and accuracy of NLR and MCTSI, as well as their alignment with the RAC for assessing AP severity. Results: In this study of 65 patients with clinically diagnosed AP, the mean age was 38.82 ± 15.82 years with a range of 15–85 years of age, with a male predominance (61.5%) and male to female ratio of 1.6:1. The study evaluated the effectiveness of MCTSI, NLR, and RAC methods for predicting the severity of AP. Severe AP cases, as classified by all methods, were associated with higher rates of surgical intervention (up to 45.5%), infection (up to 66.7%), persistent organ failure (up to 100%), mortality (up to 36.4%), and longer hospital stays (mean of up to 20.21 days), highlighting the need for accurate severity assessment in managing AP. The sensitivity, specificity, and accuracy of NLR were 67%, 90.9%, and 76%, respectively, while MCTSI had sensitivity of 95%, specificity of 13.6%, and accuracy of 62%. NLR showed a high area under the curve (0.855) compared to MCTSI (0.645). NLR was found to be a viable alternative for predicting severity, especially in resource-limited settings. Conclusion: The Modified Computed Tomography Severity Index (MCTSI) is a well-established tool for assessing the severity of AP, demonstrating ease of calculation and a close correlation with clinical outcomes. Our study confirmed that MCTSI has superior predictive ability for moderately severe and severe cases, showing high sensitivity and positive predictive value. It aligns well with the RAC, with both scoring systems significantly correlating with clinical outcomes such as the need for surgical intervention, infection, organ failure, mortality, and hospital stay duration. More adverse outcomes were observed in moderate and severe grades compared to mild cases. Additionally, NLR which is a novel parameter demonstrates strong concordance with RAC in assessing moderate-to-severe AP and offers a cost-effective alternative to MCTSI and traditional radiological methods. It can effectively predict disease severity and guide early diagnosis and treatment, particularly in settings with limited resources.